Nanotechnology based phytopharmaceuticals - A, Shanmugarathinam; E, Joshua Handel; P, Rajeevkumar; R, Poornasri (International Journal of Indigenous Herbs and Drugs, 2025)
Nanotechnology-based phytopharmaceuticals represent a cutting-edge advancement that bridges traditional herbal medicine with modern nanoscience to enhance therapeutic efficacy, safety, and patient compliance. The inherent limitations of phytoconstituents-such as poor solubility, low bioavailability, instability, and rapid metabolism-have long restricted their clinical potential. Nanotechnology enables the design of nanosized carriers, including polymeric nanoparticles, liposomes, phytosomes, nanoemulsions, solid lipid nanoparticles, dendrimers, and nanocrystals, which encapsulate, protect, and deliver plant-derived bioactives in a controlled and targeted manner. These delivery systems improve solubility, protect against enzymatic degradation, enhance permeability across biological membranes, and allow sustained drug release. Significant therapeutic applications have been reported in oncology, neurodegenerative disorders, cardiovascular protection, antimicrobial therapy, wound healing, and hepatoprotection. Despite these remarkable advantages, challenges such as large-scale production, formulation stability, toxicity assessment, and regulatory validation continue to hinder clinical translation. Thus, nanotechnology-based phytopharmaceuticals signify a paradigm shift in drug delivery science, integrating traditional plant-based medicine with precision nanotechnology to develop safer, more effective, and environmentally friendly therapies.